Representações sociais acerca da hospitalização e do adoecimento em crianças com câncer - Sallet, Sandra Regina (2018)
Introduction: The illness implies on a disruption in the way of existing as a human. It is on the relation between the experience of health and illness that is possible to learn how to deal with existential changes that are inherent to the human condition. Cancer in children implies in loss and suffering due to the long-term hospitalizations and to the constant invasive procedures and treatment complications. Objective: This investigation aimed to acknowledge children’ social representations on hospitalization and illness. Method: It consists on a qualitative research, characterized as case reports. Data analysis followed Bardin’s categorization (2015) associated to a theoretical basis anchored on Moscovici’ Social Representations Theory (2015). As for data collection, there were used the playtime and the Fairy Tales Test as instruments. Data collection was performed between March and December of 2017, where appointments were recorded and entirely reproduced so that interpretation could be led. The sample was constituted by four children with cancer who were hospitalized in a public hospital that is a reference on the treatment of cancer in children in the state of Rio Grande do Sul, Brazil. During the research, there were followed all ethical principles regarding the Resolução n° 466, from December, 12th of 2012 and the Resolução nº 510, from April, 7th of 2006, from Brazilian National Health Council, which guide ethics in research with human beings. Thus, there were respected the principles of autonomy, beneficence, non-maleficence, justice and equity, acceptation and agreement, assuring rights and duties of research participants, scientific community and the state. Results: As for the results, it is perceived that the participants of this investigation communicate their representations through opposes, denying their own illness in order to avoid fear. The knowledge on treatment ranges between the consensual universe and the reified. Findings relate comprehensions according to the time of hospitalization and development stages.